Members’ Behavior Towards Baitul Mal Wa Tamwil - Mediawati, E; Nasim, A; Agustami, S; Sholehah, W; Irwansyah Mattupuang, A; Yulia Solihati, S; Azizah, T (KnE Social Sciences, 2019)
This study aims to analyze the criteria considered by individual members in choosing Baitul Mal Wa Tamwil (BMT) and analyzing the attitudes of members towards BMT. Research subjects are individual members who use BMT services. Data analysis method is descriptive statistics. The results of the analysis concluded that there were 5 factors that were considered by the members in choosing BMT, among others: ease of obtaining business capital financing, usury-free, security, satisfying service and close to home. Religious factors are not the main reason for individual members in choosing BMT. Members consider more economic factors, namely the ease of obtaining business capital. Keywords: behavior, members, BMT, financing, usury